2021
DOI: 10.1186/s12884-021-03781-x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of labour during the COVID-19 pandemic: a national survey of impact on practice in the UK

Abstract: Background Induction of labour (IOL) is one of the most commonly performed interventions in maternity care, with outpatient cervical ripening increasingly offered as an option for women undergoing IOL. The COVID-19 pandemic has changed the context of practice and the option of returning home for cervical ripening may now assume greater significance. This work aimed to examine whether and how the COVID-19 pandemic has changed practice around IOL in the UK. Method … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Those include care provision with telemedicine, attempts to minimise the duration women spend in hospitals (either by labour induction or by discharging early after birth), changes in anaesthesia practices and reduction in the number of allowed companions during birth. [14][15][16] In an effort to minimise negative consequences, international and national guidelines were developed, modified and adapted for maternal health service provision across the entire continuum of care including antenatal care, intrapartum and postnatal care. [17][18][19][20][21] Maternity skilled health personnel (SHP)-including doctors, nurses and midwives-were at the forefront of implementing these regularly updated guidelines and faced many challenges during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Those include care provision with telemedicine, attempts to minimise the duration women spend in hospitals (either by labour induction or by discharging early after birth), changes in anaesthesia practices and reduction in the number of allowed companions during birth. [14][15][16] In an effort to minimise negative consequences, international and national guidelines were developed, modified and adapted for maternal health service provision across the entire continuum of care including antenatal care, intrapartum and postnatal care. [17][18][19][20][21] Maternity skilled health personnel (SHP)-including doctors, nurses and midwives-were at the forefront of implementing these regularly updated guidelines and faced many challenges during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for the abrupt increase in NTSV and decrease in NMETD are unclear based on these data but may be due to delay or avoidance of care, limited resources, changes in labor and delivery unit practices or management. 2 , 10 , 15 , 16 , 24 , 25 These perinatal quality indicators are reported to the Joint Commission 26 and may be available to hospitals in their hospital electronic medical records in near real-time or monthly or quarterly basis. Further, perinatal quality collaboratives 26 can play an important role in monitoring these indicators 4 , 10 , 11 , 27 and may provide guidance in quality initiatives to improve triage, labor and delivery staffing during public health emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…One Trust responded to national guidelines, while the other did not. These differences are re ected in a national study that found the majority of Trusts in the UK made no major changes to induction practices during the COVID-19 pandemic (27). National evidence also con rms the temporary cessation of home births in many areas (5).…”
Section: Continuation Of Services But Adaptation and Changementioning
confidence: 99%